2002
DOI: 10.1785/0120000920
|View full text |Cite
|
Sign up to set email alerts
|

The 1999 Mw 7.1 Hector Mine, California, Earthquake Sequence: Complex Conjugate Strike-Slip Faulting

Abstract: The 1999 M w 7.1 Hector Mine mainshock showed right-lateral strikeslip faulting, with an initial strike of N6ЊW and vertical dip. The mainshock was preceded within 20 hours by 18 recorded foreshocks of 1.5 Յ M Յ 3.8 within a few kilometers distance of the mainshock hypocenter. The aftershocks delineate how the Hector Mine earthquake ruptured with strike N6ЊW to the south for a distance of 15 km, and possibly to the north for a distance of several kilometers. The two largest aftershocks of M 5.9 and M 5.7 occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
83
0
5

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(98 citation statements)
references
References 29 publications
10
83
0
5
Order By: Relevance
“…Our estimates of fault dip are generally consistent with the aftershock distribution as shown by the cross sections in Figure 13, and positions of our major fault segments inferred from our inversion (Table 2). Aftershock positions from Hauksson et al (2002) are determined from a relocation of catalog events using a 3D velocity model of the area.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our estimates of fault dip are generally consistent with the aftershock distribution as shown by the cross sections in Figure 13, and positions of our major fault segments inferred from our inversion (Table 2). Aftershock positions from Hauksson et al (2002) are determined from a relocation of catalog events using a 3D velocity model of the area.…”
Section: Discussionmentioning
confidence: 99%
“…A later field investigation, using the coherence map from IP1 as a guide, discovered about 60 cm of rightlateral offset on this previously unreported surface rupture (Treiman et al, 2002). The central portion of the surface rupture is characterized by a localized linear zone of low coherence as the rupture crosses into the Bullion Mountains (Hauksson et al, 2002) (bottom left), and the azimuth offsets from IP1 (bottom right). (Fig.…”
Section: Observations Of Surface Deformation and Fault Rupturementioning
confidence: 97%
See 2 more Smart Citations
“…Also, variations are also due to different crustal structures, thickness, rock types, physical properties and ultimately its degree of heterogeneity. Examples of studies that document this class of b-variations include [64][65][66][67][68]. [69] have suggested that the increase in b-value is caused by the presence of uids at a particular depth in the Koyna -Warna region.…”
Section: Resultsmentioning
confidence: 99%